KAJIAN SOSIO YURIDIS PROSES PELAKSANAAN PRAPERADILAN DI PENGADILAN NEGERI BAUBAU - Done, Hardi; La Ode, Bunga Ali; Ridjalin, Dedy Sarman (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2025)
This research aims and examines the Socio Juridical Study of the Pretrial Implementation Process at the Baubau District Court. This study was carried out by combining juridical facts and field facts. Juridical facts show that every pretrial application submitted by the applicant must have a decision, whether the application is granted or rejected. After research has been carried out and this study has been compiled using field data, it will be found that if the process of arrest, detention, termination of investigation or prosecution and compensation or rehabilitation is legal, it can be concluded that: If the applicant's application is reasonable and can be proven, the pre-trial institution will issue a pre-trial decision, if it is unfounded and cannot be proven, then the judicial institution will issue a rejection decision or before the examination is complete the applicant withdraws the application or before the pre-trial examination of the main case has been submitted and heard then it will be dismissed. the pretrial application. The factors causing there to be no pre-trial decision are closely related to whether the petition is reasonable and can be proven or not or whether the applicant withdraws the petition before the case is finished or the main case has entered the trial process and has not been completed so the petition is dismissed.